2013
DOI: 10.1530/erc-13-0293
|View full text |Cite
|
Sign up to set email alerts
|

TBLR1 as an androgen receptor (AR) coactivator selectively activates AR target genes to inhibit prostate cancer growth

Abstract: Androgen Receptor (AR), a steroid hormone receptor, is critical for prostate cancer growth. However, activation of AR by androgens can also lead to growth suppression and differentiation. Transcriptional cofactors play an important role in this switch between proliferative and anti-proliferative AR target gene programs. TBLR1, a core component of the nuclear receptor corepressor (NCoR) complex, shows both co-repressor and co-activator activities on nuclear receptors, but little is known about its effects on AR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 32 publications
1
35
0
Order By: Relevance
“…Moreover, the functions of TBL1XR1 were distinct in different tumors. In prostate cancer, TBL1XR1 was reported to function as a tumor suppressor and inhibit tumor growth, perhaps through regulating androgen receptor (AR) signaling pathway (Daniels et al 2014. However, TBL1XR1 has been reported to be highly expressed in cervical cancer , breast cancer , nasopharyngeal carcinoma , hepatocellular carcinoma (Kuang et al 2016), digestive cancers (Liu et al 2016a;Zhou et al 2016;Liu et al 2017), and ovarian cancer .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the functions of TBL1XR1 were distinct in different tumors. In prostate cancer, TBL1XR1 was reported to function as a tumor suppressor and inhibit tumor growth, perhaps through regulating androgen receptor (AR) signaling pathway (Daniels et al 2014. However, TBL1XR1 has been reported to be highly expressed in cervical cancer , breast cancer , nasopharyngeal carcinoma , hepatocellular carcinoma (Kuang et al 2016), digestive cancers (Liu et al 2016a;Zhou et al 2016;Liu et al 2017), and ovarian cancer .…”
Section: Introductionmentioning
confidence: 99%
“…Previously our lab showed that TBLR1 was expressed as both nuclear and cytoplasmic protein [15]. In PCa cells, nuclear expression of TBLR1 was significantly reduced in comparison to benign prostate cells.…”
Section: Resultsmentioning
confidence: 99%
“…Previously our lab showed that overexpression of nuclear TBLR1 in AD LNCaP cells inhibited growth in an androgen-dependent manner by cell cycle arrest but this overexpression had no effect on apoptosis [15]. To test the function of cytoplasmic TBLR1, we created stable LNCaP cell lines overexpressing TBLR1 in the cytoplasm utilizing a fusion construct of the nuclear export sequence (NES) (MLQKKLEELE) to the N-terminus of TBLR1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations